2001
DOI: 10.1006/jagm.2000.1135
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Aspect Ratio Trees: Combining the Advantages of k-d Trees and Octrees

Abstract: Given a set S of n points in lRd, we show, for fixed d, how to construct in O(n log n) time a data structure we call the Balanced Aspect Ratio (BAR) tree. A BAR tree is a binary space partition tree on S that has O(logn) depth and in which every region is convex and "fat" (that is, has a bounded aspect ratio). While previous hierarchical data structures, such as k-d trees, quadtrees, octrees, fair-split trees, and balanced box decompositions can guarantee some of these properties, we know of no previous data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 31 publications
3
61
0
Order By: Relevance
“…To compute an SSPD for a given point set S, we use a bounded aspect ratio (BAR) tree, as introduced by Duncan et al [11]. A BAR-tree for a point set S is a binary space partition (BSP) tree with the following properties: Let T be a BAR-tree on the point set S. For a node ν, we use pa(ν) to denote the parent of ν, and we use S(ν) to denote the subset of points from S that are stored in the leaves of the subtree T ν rooted at ν.…”
Section: Computing An Sspd In R Dmentioning
confidence: 99%
See 1 more Smart Citation
“…To compute an SSPD for a given point set S, we use a bounded aspect ratio (BAR) tree, as introduced by Duncan et al [11]. A BAR-tree for a point set S is a binary space partition (BSP) tree with the following properties: Let T be a BAR-tree on the point set S. For a node ν, we use pa(ν) to denote the parent of ν, and we use S(ν) to denote the subset of points from S that are stored in the leaves of the subtree T ν rooted at ν.…”
Section: Computing An Sspd In R Dmentioning
confidence: 99%
“…According to Lemma 16 summation (6) Proof The proof is the same as the proof of Lemma 3.10 from [2] where the dependency on the dimension follows from plugging in Corollary 3 and the fact that the BAR tree T requires O(d2 d n log n) time to compute [11].…”
Section: D(r(pa( ν)) R(pa( μ)))mentioning
confidence: 99%
“…In this paper we present the BAR tree in IR 2 . The generalized BAR tree in IR d is presented in [9]. The construction of the BAR tree is very similar to that of a k-d tree, except for two important differences:…”
Section: The Balanced Aspect Ratio (Bar) Treementioning
confidence: 99%
“…Approximate nearest neighbor queries in spaces of fixed dimension have been widely studied. Data structures with O(n) storage space and query times no better than O(log n+1/ε d−1 ) have been proposed by several authors [8,9,11,15]. In subsequent papers, it was shown that query times could be reduced, at the expense of greater space [10,19,13,23].…”
Section: Introductionmentioning
confidence: 99%